Valorisation of olive pomace by solid-state fermentation with Aspergillus species for lipase production - Oliveira, Felisbela Maria Araújo (2013)
Pollution by olive mill wastes is a crucial problem in Mediterranean area and their proper management and utilization is demanded. Olive pomace offers excellent properties to produce enzymes by solid-state fermentation (SSF) using filamentous fungi. Particularly for lipase production, since it has residual content of olive oil. The aim of this work was to optimize the production of lipase by Aspergillus ibericus MUM 03.49, Aspergillus niger MUM 03.58 and Aspergillus tubingensis MUM 06.152, under SSF of olive pomace. A Taguchi L-9 orthogonal array based on 4 factors at 3 levels (ratio between olive pomace and wheat bran (OP:WB), NaNO3, Czapek nutrients and time) was implemented. SSF was carried out in Erlenmeyer flasks of 500 mL and lipase activity was measured using p-nitrophenyl butyrate as substrate. Results showed for all fungi that the factor with most significant effect on lipase production was the mixture OP:WB, concluding that the presence of wheat bran on substrate favored lipase production. NaNO3 concentration and time presented some effect and presence of Czapek nutrients did not added significant advantages on lipase production. A. ibericus was the best lipase producer, being a promising microorganism for lipase production. Under optimized conditions it produced 20.78 U/gds of lipase.